Current Potential of Pantoprazole in Treatment and Prevention of Gastrointestinal Diseases - A. A. Sheptulin; S. S. Kardasheva; A. A. Kurbatova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2021)
Aim. An outline of the current potential of pantoprazole in treatment and prevention of upper gastrointestinal diseases.Key points. Pantoprazole is widely applied in gastroesophageal reflux, peptic ulcer disease, Zollinger—Ellison syndrome and for Helicobacter pylori eradication. It minimally inhibits the CYP2C19 isoenzyme involved in the metabolism of many drugs. Pharmacokinetics of pantoprazole conditions a weaker drug interaction compared to other proton pump inhibitors (PPIs), which enables its use for gastrointestinal bleeding prevention in patients receiving dual antiplatelet therapy. The new coronaviral pandemic of COVID-19 urges the selection of PPIs that minimise the drug interference, such as pantoprazole, in therapy and prevention of acid-related upper gastrointestinal diseases. Pantoprazole has a good tolerance and low side effect rate.Conclusion. Pantoprazole is considered among optimal PPIs for efficacy, safety and adherence on the basis of clinical trials for treatment and prevention of gastrointestinal diseases, systematic reviews and meta-analyses.